Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

simplify this step by step
[tex] \frac{-5jk}{35j^2k^2} [/tex]


Sagot :

[tex]\dfrac{-5jk}{35j^2k^2}=-\dfrac{1}{7jk}[/tex]
[tex]\frac { -5jk }{ 35{ j }^{ 2 }{ k }^{ 2 } } \\ \\ =-\frac { 5 }{ 35 } \cdot \frac { j }{ { j }^{ 2 } } \cdot \frac { k }{ { k }^{ 2 } } \\ \\ =-\frac { 1 }{ 7 } \cdot \frac { 1 }{ j } \cdot \frac { 1 }{ k } \\ \\ =-\frac { 1 }{ 7jk }[/tex]

Remember that:

[tex]\frac { j }{ { j }^{ 2 } } =\frac { 1 }{ j } \cdot \frac { j }{ j } =\frac { 1 }{ j } \cdot 1=\frac { 1 }{ j } \\ \\ \frac { k }{ { k }^{ 2 } } =\frac { 1 }{ k } \cdot \frac { k }{ k } =\frac { 1 }{ k } \cdot 1=\frac { 1 }{ k }[/tex]